Tumor-Receptor Imaging in Breast Cancer: A Tool for Patient Selection and Response Monitoring - Heskamp, S.; W.M. van Laarhoven, H.; J.G. Oyen, W.; T.A. van der Graaf, W.; C. Boerman, O. (Current Molecular Medicine, 2013)
Breast cancer is a heterogeneous disease that can be subdivided into different groups, based on gene expression profiles or clinicopathological characteristics such as estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) expression. The expression of these receptors has both prognostic and predictive value. To improve breast cancer treatment, accurate methods for patient selection and response monitoring are required. One way to achieve this is by using molecular imaging, which can be used to measure the expression and accessibility of tumor-associated antigens in vivo, without the need of invasive biopsies. This review will focus on tumor-receptor imaging for currently approved targeted therapies and discuss the potential role of molecular imaging in the development of new therapeutic agents in breast cancer. Progress has been made in radionuclide imaging of ER, PR, HER2 and epidermal growth factor receptor (EGFR) expression, which can be used for treatment selection and response prediction to endocrine and other targeted therapy. Moreover, clinical studies have shown the feasibility for molecular imaging of the angiogenic pathway exploiting the expression of antigens closely associated with angiogenesis, such as αvβ3 and VEGF. As proof of concept has been established, further research should be directed towards validation of the imaging methods and the impact on patient management.
Keywords: molecular imaging